TECHNOLOGICAL ADVANCEMENT IN MEDICAL ENGINEERING - Asnida Abdul Wahab, 1984-, editor 599072 (Skudai, Johor : Penerbit UTM Press, 2017)
Medical engineering has been constantly expanded due to the rapid evolution of modern healthcare system and industry around the world. New medical applications development and techniques have brought together the best and brightest of society in improving the quality of human life. This book provides the latest insight of medical engineering interdisciplinary topics including ankle exercise rehabilitation, balance and stability assessment, and development of a smart medical alerting system for diabetic patients. Interesting topics on the modified biomaterial in preventing biofilm formation, application of bioluminescence in biomedical research, and transformation of patient and content management using the current technology available, are also discussed in this book. All chapters were exquisitely incorporated to guide the readers in understanding the overall content. This book is certainly a valuable piece for biomedical engineering students, lecturers, researchers and biomedical engineers who need to update themselves with the latest research trend in the medical engineering field.